Prevalence of KPC-producing bacteria in negative gram of clinical samples obtained from patients. (May 2022) - Kharazmkia, Ali; Amirizadeh, Mehran; Goudarzi, Zahra; Birjandi, Mehdi; Barfipoursalar, Alireza; Mir, Samareh
Abstract: Objective: Carbapenems are beta-lactam antibiotics that can play an important role in infections with multiple and severe resistance. The aim of this study was to investigate the frequency of carbapenem-producing bacteria in gram-negative isolates of clinical samples obtained from patients. Methods: 291 g-negative bacilli were isolated from the samples of hospitalized patients using gram staining method, conventional methods and biochemical tests. The antibiotic susceptibility of the isolates was determined using the agar disk diffusion method for 5 different antibiotics. Strains that were resistant to Meropenem antibiotic, KPC enzyme production was examined by the Modified Hodge test method. Results: Out of 291 g-negative bacilli, 14 isolates showed resistance to Meropenem by a disk agar diffusion method where 12 (85.8%) strains were producing KPC enzyme. The highest frequency of Gram-negative KPC-producing bacilli was related to Klebsiella pneumoniae and the most positive samples were urine. The prevalence of this type of bacteria was highest in NICU and the male internal ward, respectively. Conclusion: It was shown that carbapenem-resistant strains are considered as a growing problem in hospitals, especially in the intensive care unit for children and men. Highlights: Carbapenems are beta-lactam antibiotics that can play an important role in infections with multiple and severe resistance. The circulation of carbapenem-resistant Klebsiella pneumonia is a significant problem worldwide. The present study focused on the carbapenemase production among Gram-negative isolates in Human samples. It was shown that carbapenem-resistant strains are considered as a growing problem in hospitals. Between KPC-producing gram-negative bacilli and the type of sample, and urine samples were the most common.